An Investigation on English Teacher’s Strategies for Speaking Activities at SMA Muhammadiyah 6 Palembang - Rizki Priatna (Ta'dib: Jurnal Pendidikan Islam, 2022)
By incorporating an English teacher and a class of 30 students, this study aims to represent teacher practices in teaching speaking to students at SMA Muhammadiyah 6. This qualitative research is in the form of a case study. An English teacher was chosen by using purposive sampling as the participant on this study. A semi-structured interview was used to gather data and identify teaching tactics for speaking. The data were then discussed by using thematic analysis. The results demonstrated that the teacher employed a variety of strategies, including group discussion, brainstorming, and storytelling. The teacher used the strategies to encourage students to participate in the learning process. Because the strategies were implemented properly, they might be able to assist students in becoming more involved in the teaching and learning process